OBSERVANCE AND NON-OBSERVANCE OF GRICEAN MAXIMS IN FAMILY DIALOGUE IN EUGENE O’NEILL’S LONG DAY’S JOURNEY INTO NIGHT - Irza Firmandi Majid; Nur Fitria Anggrisia; Satria Adi Pradana (PARADIGM: Journal of Language and Literary Studies, 2026)
Family communication in literary works often reflects hidden emotional conflict, denial, and psychological tension expressed through indirect language and implied meaning. Within literary pragmatics, discussions of Grice’s cooperative principle have mostly focused on films, advertisements, and educational discourse, while emotionally conflicted family dialogue in drama remains less explored, particularly in relation to both observance and non-observance of conversational maxims. This article examines how the characters in Eugene O’Neill’s Long Day’s Journey into Night employ conversational strategies to maintain relationships, avoid confrontation, and express emotional suffering. The study is based on qualitative data collected from 21 selected dialogues in the drama script and analyzed interpretively using Grice’s cooperative principle as the main theoretical foundation. Cutting’s framework was used to elaborate the observance of Gricean maxims, while Nemesi’s classification was used to examine the forms of Gricean maxim non-observance. The findings reveal that the characters simultaneously observe and fail to observe conversational maxims in emotionally tense interactions. Observance of maxims is mainly used to maintain conversational continuity and emotional connection, while non-observance, particularly violation and exploitation, functions as a strategy for denial, sarcasm, emotional defense, and concealment of painful realities. These findings demonstrate that pragmatic strategies in dramatic dialogue closely reflect fractured family relationships and unresolved psychological trauma.